Biopolicy the life sciences and public policy - Somit, Albert; Peterson, Steven A. (Bingley, U.K. : Emerald, 2012)
Biology can inform public policy in a number of ways. This volume explores the linkage of the life sciences with policy (what the book refers to as biopolicy). It features two points of departure: the implications of the neurosciences for public policy; and the implications of evolutionary theory for policy-making. The first part of the book provides an introduction to the subject of biopolicy as well as the relevance of the brain sciences and evolutionary theory for this subject. The second part considers several case studies of how these points of departure inform our knowledge of policy. Among case studies provided here are the implications for distribution of wealth, the roots of foreign policy, violent behavior, policy decision-making, and the like. In the final analysis, this book provides examples of how the life sciences can inform public policy choices. Research in Biopolitics is the only book series that focuses specifically on the relationship between biology and politics, and provides contemporary research for practitioners, including anthropologists, sociologists, economists, biopolitical researchers, as well as students of law and political science.
Biopolicy: A Critical Linkage / Albert Somit, Steven A. Peterson -- The Cooperative Gene: Evolution, Human Nature, and Politics / Peter A. Corning -- The Brain and Public Policy / Robert H. Blank -- Evolution, IQ, and Wealth / Tatu Vanhanen -- Evolution and Foreign Policy: Insights for Decision-making Models / John M. Friend, Bradley A. Thayer -- Neurotoxicity and Public Policy: Linking Brain Chemistry, Toxins, and Violent Crime / Roger D. Masters -- From Embodiment to Public Policy: The Intersection of Individual Physiology, Psychology, and Institutional Policy Behaviors / Matthew P. Cantele, Rebecca J. Hannagan, Douglas R. Oxley -- Driving the Great Apes to Extinction: Perspectives from Conservation Biology, Politics, and Bioethics / Judith Benz-Schwarzburg, Sophia Benz -- Leadership and Economics from a Behaviorist Perspective / Nancy E. Aiken -- Make Up your Own Mind: The Politics of Cognitive Freedom / Amy L. Fletcher.
Print version record
Keywords: Business & Economics -- Accounting -- General; Business & Economics -- Accounting -- Managerial; Accounting; Management accounting & bookkeeping; Biopolitics; Life sciences